A Multidisciplinary Patient Navigation Program Improves Compliance With Adjuvant Breast Cancer Therapy in a Public Hospital. (July 2017) - Castaldi, Maria; Safadjou, Saman; Elrafei, Tarek; McNelis, John
Cancer health disparities affecting low-income and minority patients have been well documented to lead to poor outcomes. This report examines the impact of patient navigation on adherence to prescribed adjuvant breast cancer treatment. A multidisciplinary patient navigation program was initiated at a public safety net hospital to improve compliance with 3 National Quality Forum measures: (1) administration of combination chemotherapy for women with Stage (defined by the American Joint Committee on Cancer [AJCC]) T1c, II, or III hormone receptor-negative breast cancer within 120 days; (2) administration of endocrine therapy for women with AJCC Stage T1c, II, or III hormone receptor-positive breast cancer within 365 days; and (3) radiation therapy for women receiving breast-conserving surgery within one year. Implementation of a multidisciplinary patient navigation program reduced time to treatment and improved compliance with adjuvant therapy for breast cancer in an underserved minority community.